Absolute structures and bioactivities of euryspongins and eurydiene obtained from the marine sponge Euryspongia sp. collected at Iriomote Island. Issue 4 (15th February 2015) - Yamazaki, Hiroyuki; Takahashi, Ohgi; Kanno, Syu-ichi; Nakazawa, Takahiro; Takahashi, Shiori; Ukai, Kazuyo; Sumilat, Deiske A.; Ishikawa, Masaaki; Namikoshi, Michio
Graphical abstract: Abstract: Three unique sesquiterpenes, named euryspongins A–C (1 –3 ), have been isolated from the marine sponge Euryspongia sp. The absolute configuration of1 was assigned as (4 R, 6 R, 9 S ) by comparing its experimental Electronic Circular Dichroism (ECD) spectrum with the calculated ECD spectra of both enantiomers, and the absolute configurations of2, 3 and artifact4 were suggested on the basis of that of1 by assuming common biogenesis of1 –3 . These absolute configurations were opposite to those depicted in the previous communication. Further separation of the remaining fractions lead to the isolation of a new C11 -polyketide, named as eurydiene (5 ), together with a known C11 -polyketide, nakitriol (6 ). The structure of5 was assigned on the basis of its spectroscopic data as a bicyclic alcohol with a diene side chain. Dehydroeuryspongin A (4 ) inhibited protein tyrosine phosphatase 1B (PTP1B), an important target enzyme for the treatment of type II diabetes and obesity, with an IC50 value of 3.58 μM. Moreover, compound4 did not inhibit the proliferation of human hepatoma Huh-7 cells at 100 μM. One of the locations in which PTP1B has been detected is hepatocytes. Compounds1 –3, 5, and6 were not active against PTP1B. The growth of human colon (HCT-15) and T-cell lymphoma (Jurkat) cells was not disturbed by compounds1 –6 .